Nourishing healthcare information over Facebook - Adzharuddina, Nor Azura; Mohd Ramly, Norazmie (Elsevier (ScienceDirect), 2014)
This study is based on the review of literature, focusing on new media namely Facebook in sustaining and nourishing healthcare information to its users. This is to recognise the capability of Facebook in providing health information and contribute to further awareness on healthcare, nutrition, diet, diseases and remedy information. In addition, it also examines health-related Facebook pages administered by healthcare providers for example specialist, physician, nutritionist or dietician in disseminating information mainly on health; in creating awareness and encouraging behavioural changes. Facebook pages with health-related information were discussed to see how they can be beneficial to new media users.